Stress and fracture analysis of short flat bars with projections using boundary element method (BEM) - Hu, Zheng Jie. (2010)
Stress and fracture analysis were carried out on short flat bars with projections using boundary element method. The short flat bar was subjected to either axial tensile loading or shear loading at the shank with either remote or local restraint at the head and shoulder respectively. Crack was modeled at the fillet area where high stress concentration is located. The computational results for stress concentration factor and stress intensity factor that were obtained in the analyses were compared with published data using finite element analysis in the literature. It was found that they are in good agreement.